2014
DOI: 10.1097/jsa.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Elbow Injuries in Athletes

Abstract: Elbow injuries in pediatric and adolescent population represent a spectrum of pathology that can range from medial tension injuries to posterior shear injuries. Elbow injuries in this population continue to rise in parallel with the increase in youth participation in sports both throughout the calendar year and across multiple sports. Many of these injuries are noncontact and are attributed to overuse. Evaluation and management of youth and adolescent athletic elbow injuries requires knowledge of developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The significance of this finding is unclear, but may reflect institutional practice patterns, or the changing pattern of sports participation and injury in children. With increased participation at a higher level of sport, greater forces and injury patterns are occurring, 11 potentially leading to greater instability and need for rigid fixation. This observation will need to be validated in future prospective studies.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of this finding is unclear, but may reflect institutional practice patterns, or the changing pattern of sports participation and injury in children. With increased participation at a higher level of sport, greater forces and injury patterns are occurring, 11 potentially leading to greater instability and need for rigid fixation. This observation will need to be validated in future prospective studies.…”
Section: Discussionmentioning
confidence: 98%
“…As the patient's pain resolves and range of motion improves, strengthening exercises of the forearm pronator and wrist flexor musculature should begin. When the patient is asymptomatic, an interval throwing program can be initiated to prepare the athlete to return to sports [3]. Research in the pediatric population is limited, but adult nonthrowing athletes who sustain a traumatic UCL injury are able to return to sports quicker and with better functional outcomes than adult throwing athletes [40].…”
Section: Elbow Injuriesmentioning
confidence: 99%
“…Surgical repair or reconstruction should be considered for chronic instability, acute full‐thickness tears, tears in high‐demand overhead athletes, or failed rehabilitation. After UCL reconstruction or repair, 80%‐90% of athletes are able to return to their preinjury functional status; however, athletes should be counseled that it typically requires at least 1 year to achieve maximal function after surgery [3,8,42].…”
Section: Elbow Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…7,16,23 Although the direct effect of this noncompliance has not yet been elucidated, the connection of overuse to upper extremity injuries among amateur pitchers has been well established. 5,8,12,13,17,18,21 As these injuries continue to occur in these athletes, the need for surgical intervention will likely continue to climb. Fortunately, multiple studies showed encouraging results of UCL reconstructive surgery for amateur baseball players.…”
mentioning
confidence: 99%